دور مقاصد الشريعة في بناء الحضارة الإنسانية - حدد, فخر الدين (University of Eloued جامعة الوادي, 2017)
لقد شغل موضوع التحضر بال كثير من الناس وخاصة العلماء منهم، وأسال النقاش حوله الكثير من الحبر، كل يدلي بدلوه للإدلاء برأيه فيه، سواء لشرحه وبيان المراد منه، أم لاتخاذ موقف واضح حوله، إما إيجابي أو سلبي. ولكن المطّلع على الاختلاف الذي حصل حول موضوع التحضر يجد أن هذا الاختلاف اختلاف لم يحرّر فيه موطن النزاع، ذلك أن التحضر الحقيقي لا ينبغي أن يُختَلف فيه، بل المطلوب أن يحصل حوله اتفاق؛ ذلك أنّ التحضر الحقيقي هو ما كان منطلقه دينيا وخضع لسلطان الأخلاق والفضائل، وما لم يكن كذلك فلا يصح تسميته تحضرا أصلا، بل يمكن أن يطلق عليه تسميات أخرى، مثل: التمدن، أو الحداثة أو التطور المادي، أو غير ذلك. ولهذا فقد كانت الحضارة الإسلامية أعظم الحضارات وأكثرها نفعا للبشرية؛ لأنها اشتملت على خصائص حضارية لم تشهدها أي حضارة لا قديما ولا حديثا، ذلك لأنّ مصدرها رباني، وتعاليمها مستمدة من الوحي، وما كان كذلك فإنه خير كله سواء في العاجل أم الآجل. ومنه فإن المقاصد العامة للشريعة الإسلامية قد ساهمت مساهمة كبيرة وفعالة في إرساء قواعد الفعل الحضاري، وتطوير النشاطات الحضارية وتهذيبها وإصلاح ما فيه خلل منها، بما يعود بالخير والسعادة للبشرية، لأن ما اعتبره بعض الناس تحضرا ليس هو كذلك عند تدقيق النظر، ولهذا احتاج الناس إلى توجيه رباني وإرشاد سماوي يميزون به بين الحق والباطل، وبين الغث والسمين في موضوع التحضر، كيلا يقعوا فيما لا تُحمد عقباه، وهو الدور الذي قامت به مقاصد الشريعة الإسلامية على أكمل وجه.The subject of urbanization has occupied many people, especially scientists and the discussion about it has poured a lot of ink all make his own contribution to according his opinion everyone either to explain and indicate the meaning of it, or to take a clear; negative or positive .But who is familiar with the difference about the topic of urbanization finds that this difference has not been identified urbanization should not be different, but to get an agreement about it that real urbanization is what was religiously motivated and goes under the rule of morals and virtues otherwise it is not correct to call it civilized, but might be called other labels, such as modernity, or physical development, or something else and that Islamic civilization has been the greatest and most beneficial cultures. Of humanity; they included urban properties not seen in any civilization not old not recently, because their source, and their teachings derived from revelation, and what was it all good soon or later. And of the general purposes of Sharia It has contributed greatly to the establishment of the rules of civilizational action, and the development of civilized activities and the reform and repair of what is flawed, including the good and happiness of mankind, why what some people consider civilized not so when checking between the right and wrong, and the bad and good on the subject of urbanization, So that they do not fall in what is undesirable which is the role played by the purposes of Islamic law to the fullest.
مذكرةماستر تخصص اصول فقه
Keywords: : مقاصد الشريعة، الحضارة، التحضر، الحضارة الإسلامية، الخصائص، دور المقاصد.; The purposes of Sharia, civilization, urbanization, Islamic civilization, characteristics, the role of purposes